2018
DOI: 10.3390/molecules23020274
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Characterization and Identification of Non-Diterpenoid Constituents in Tinospora sinensis by HPLC-LTQ-Orbitrap MSn

Abstract: Tinospora sinensis, a kind of Chinese folk medicine, has functions of harmonizing qi and blood, dredging the channels and collaterals, calming and soothing the nerves. In the present study, a method based on high-performance liquid chromatography coupled with linear ion trap-Orbitrap mass spectrometry (HPLC-LTQ-Orbitrap) was developed for the systematical characterization of the non-diterpenoid constituents which possessed remarkable biological activities in T. sinensis, like anti-tumor, anti-inflammatory, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Eleven components were identified from the methanol extract of liverwort and four components were identified from the methanol extract of Racomitrium moss. In positive mode ionization, the mass data show a similar fragmentation profile with m/z at 543, 527, and 381, which is correlated to pinoresinol-di- O - β -D-glucopyranoside ( Figure 11 ) [ 40 ]. Pinoresinol-di- O - β -D-glucopyranoside exhibited remarkable inhibitory activity against the production of PGE 2 in LPS-induced RAW264.7 cells [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven components were identified from the methanol extract of liverwort and four components were identified from the methanol extract of Racomitrium moss. In positive mode ionization, the mass data show a similar fragmentation profile with m/z at 543, 527, and 381, which is correlated to pinoresinol-di- O - β -D-glucopyranoside ( Figure 11 ) [ 40 ]. Pinoresinol-di- O - β -D-glucopyranoside exhibited remarkable inhibitory activity against the production of PGE 2 in LPS-induced RAW264.7 cells [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another fourteen known compounds were identified as patuletin ( 3 ) [15], quercetin ( 4 ) [16], quercetin-3-O-α-L-arabinopyranoside ( 5 ) [17], quercetin-7-O-α-L-rahmnoside ( 6 ) [18], kaempferol ( 7 ) [19], kaempferol-3-O- β -D-glucoside ( 8 ) [20], kaempferol-3-O-α-L-arabinopyranoside ( 9 ) [21], kaempferol-7-O-α-L-rahmnoside ( 10 ) [22], kaempferol-3-O- β -D-xylopyranoside ( 11 ) [23,24], 1- β -D-glucopyranosyl-2, 6-dimethoxy-4-propenylphenol ( 12 ) [25], syringaresinol-4′-O- β -D-glucoside ( 13 ) [26], 4-allyl-2, 6-dimethoxy phenyl glucoside ( 14 ) [27], 2-methoxy-4-(2-propenyl) phenyl- β -D-glucoside ( 15 ) [28], and 6-methoxy–kaempferol-7- β -D-glucoside ( 16 ) [29], based on the analysis of their 1D and 2D NMR, MS, as well as other spectroscopies.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 However, due to the complexities and diversities of its chemical constituents, the effective constituents and their molecular mechanisms for its anti-arthritis effect are still poorly understood. 6,7 According to the previous report, the EtOAc fraction of ethanolic extract from the stems of T. sinensis exhibited an anti-arthritis effect, which might be attributed to inhibiting the production of pro-inammatory cytokines and down-regulating the MAPK signaling pathway, and suggested that avonoids including rutin, quercetin and isorhamnetin might be the mainly effective constituents in the crude extracts. 3 But actually, the chemical compositions of T. sinensis were very complicated, which contained terpenoids such as sesquiterpenoids, diterpenoids and triterpenoids, lignans, alkaloids, avonoids and so on.…”
Section: Introductionmentioning
confidence: 97%
“…3 But actually, the chemical compositions of T. sinensis were very complicated, which contained terpenoids such as sesquiterpenoids, diterpenoids and triterpenoids, lignans, alkaloids, avonoids and so on. 6 Among them, diterpenoids and lignans were abundant in T. sinensis. Therefore, in order to have a fully understanding of these two classes of compounds in T. sinensis, a phytochemical reinvestigation of T. sinensis was undertaken, resulting in the isolation of twenty-two compounds, including sixteen lignans (1-2, 9-22) and six clerodane diterpenoid glucosides (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation